Week 96 results of the randomized, multicentre Maraviroc Switch (MARCH) study. Issue 1 (13th July 2017) - Pett, SL; Amin, J; Horban, A; Andrade‐Villanueva, J; Losso, M; Porteiro, N; Madero, JS; Belloso, W; Tu, E; Silk, D; Kelleher, A; Harrigan, R; et al.
Abstract : Objectives: The Maraviroc Switch (MARCH) study week 48 data demonstrated that maraviroc, a chemokine receptor‐5 (CCR5) inhibitor, was a safe and effective switch for the ritonavir‐boosted protease inhibitor (PI/r) component of a two nucleos(t)ide reverse transcriptase inhibitor [N(t)RTI] plus PI/r‐based antiretroviral regimen in patients with R5‐tropic virus. Here we report the durability of this finding. Methods: MARCH, an international, multicentre, randomized, 96‐week open‐label switch study, enrolled HIV‐1‐infected adults with R5‐tropic virus who were stable (> 24 weeks) and virologically suppressed [plasma viral load (pVL) < 50 HIV‐1 RNA copies/mL]. Participants were randomized to continue their current PI/r‐based regimen (PI/r) or to switch to MVC plus two N(t)RTIs (MVC) (1:2 randomization). The primary endpoint was the difference in the proportion with pVL < 200 copies/mL at 96 weeks. The switch arm was defined as noninferior if the lower limit of the 95% confidence interval (CI) for the difference was < −12% in the intention‐to‐treat (ITT) population. Safety endpoints (the difference in the mean change from baseline or a comparison of proportions) were analysed as key secondary endpoints. Results: Eighty‐two (PI/r) and 156 (MVC) participants were randomized and included in the ITT analysis; 71 (87%) and 130 (83%) were in follow‐up and on therapy at week 96. At week 96, 89.0% and 90.4% in the PI/r and MVC arms, respectively, had pVL < 50 copies/mL (95% CI ‐6.6, 10.2). Moreover, in those switching away from PI/r, there were significant reductions in mean total cholesterol (differences 0.31 mmol/L; P = 0.02) and triglycerides (difference 0.44 mmol/L; P < 0.001). Changes in CD4 T‐cell count, renal function, and serious and nonserious adverse events were similar in the two arms. Conclusions: MVC as a switch for a PI/r is safe and effective at maintaining virological suppression while having significant lipid benefits over 96 weeks.